An Educational Serious Game for investigating perceived Impacts of Digital Technologies on Employee Well-Being and Organizational Performance - Herrmann, Jan-Phillip; Nemoto, Y.; Kobelt, Dennis; Goppold, M.; Tackenberg, Sven (Gemeinschaften in Neuen Medien : Digitale Partizipation in hybriden Realitäten und Gemeinschaften)
The worldwide digitalization of companies changes work processes and organization of work. Digital technologies will improve productivity, efficiency, and ergonomics at the workplace. In higher education of industrial engineering, students need to reflect positive and negative consequences when designing work systems. The initial success of technological solutions depends on people's attitude towards their actual benefit (Venkatesh & Bala, 2008). Some studies suggest that people's attitude changes with cultural background (Straub, Keil & Brenner, 1997). There is little research in an educational context on how people perceive digital technologies' impact on employee well-being and organisational performance, and how this perception differs based on culture. Therefore, this study investigates these differences from an intercultural perspective by comparing German and Japanese engineering students. Referring to problem-based learning, we present a serious game that confronts players with solving fictive problems of a manufacturer of refrigerators by choosing between technological and traditional solutions. Initially, players choose individual well-being and organisational performance criteria out of a set of possible criteria. In four subsequent rounds, players pick a problem card that they have to solve using technological or traditional solutions. Players assess the impact of their choice considering their initially selected criteria of individual well-being and organisational performance. A player wins by achieving the highest score, which results from how well players solve their problems with the given solutions and how well these influence their initially selected criteria. A software supports the game by computing each players’ score and storing the game data. The purpose of the serious game is twofold. First, incorporating the serious game into teaching allows supporting multiple dimensions of learning goals (cf. Krathwohl, 2002) and stimulating students' learning processes. Second, it enables data collection about players' perceived impacts of digital technologies on employee well-being and organisational performance. We describe the game rules and processes and discuss implications in the learning processes of students crossing boundaries. We present the results of playing the game with 43 students in Germany and 60 students in Japan by analysing the two games' collected data individually and by comparing the results.